ANALYSIS OF INFLUENCE OF STRATEGIC ACTION, KNOWLEDGE MANAGEMENT ORIENTATION AND INNOVATION IN LOGISTICS TO FIRM PERFORMANCE (Study at Sea Transportation Service Company Operating In Port of Tanjung Emas Semarang) - Ismail, Fajar; Kusumawardhani, Amie; Sugiono, Sugiono (JURNAL BISNIS STRATEGI, 2017)
This research is motivated by the number of Sea Transportation Service (JPT) companies operating in the port of Tanjung Emas which lost their revenue for 6 months in a row, resulting in the revocation of their permits. The inability to compete in the form of low operational performance leads to a decrease in financial performance. Some researchers believe that innovation in logistics is the most effective way of increasing competitive advantage and firm performance in the logistics industry.Therefore, this study aims to analyze the relationship between innovation in logistics, operation performance, and financial performance and the factors that influence innovation is strategic action and knowledge management orientation. The data were obtained from a questionnaire filled by 178 Sea Management Services (JPT) companies operating in the Port of Tanjung Emas Semarang. Data were analyzed with Structural Equation Modeling (SEM) using AMOS software.The result of the statistical analysis shows that directly strategic action and innovation in logistics have a positive and significant effect on operational performance. Indirectly knowledge management orientation has a positive and significant effect on operational performance through innovation in logistic.